The Mst1 Kinase Is Required for Follicular B Cell Homing and B-1 B Cell Development - Alsufyani, Faisal; Mattoo, Hamid; Zhou, Dawang; Cariappa, Annaiah; Van Buren, Denille; Hock, Hanno; Avruch, Joseph; Pillai, Shiv (Frontiers in Immunology, 2018)
The Mst1 and 2 cytosolic serine/threonine protein kinases are the mammalian orthologs of the Drosophila Hippo protein. Mst1 has been shown previously to participate in T-cell and B-cell trafficking and the migration of lymphocytes into secondary lymphoid organs in a cell-intrinsic manner. We show here that the absence of Mst1 alone only modestly impacts B cell homing to lymph nodes. The absence of both Mst1 and 2 in hematopoietic cells results in relatively normal B cell development in the bone marrow and does not impact migration of immature B cells to the spleen. However follicular B cells lacking both Mst1 and Mst2 mature in the splenic white pulp but are unable to recirculate to lymph nodes or to the bone marrow. These cells also cannot traffic to the splenic red pulp. The inability of late transitional and follicular B cells lacking Mst 1 and 2 to migrate to the red pulp explains their failure to differentiate into marginal zone B cell precursors and marginal zone B cells. Mst1 and Mst2 are therefore required for follicular B cells to acquire the ability to recirculate and also to migrate to the splenic red pulp in order to generate marginal zone B cells. In addition B-1 a B cell development is defective in the absence of Mst1.